Junior High School Students’ Mathematical Modelling Ability in Solving Geometry and Measurements Problems on Asesmen Kompetensi Minimum - Maulani, Silvia Fajar; Hidayat, Dayat; Fardah, Dini Kinati (Universitas Islam Negeri Sunan Kudus, 2023)
The connection between mathematics and the application of mathematical concepts affects all aspects of daily life. Because of the connection between mathematics and the real world through mathematical models, mathematical modelling may help students in understanding this relationship. In the context-based Asesmen Kompetensi Minimum (AKM) problems, students are asked to solve mathematical problems related to the real world. This study aims to determine the mathematical modelling ability of grade VIII junior high school students in solving AKM problems. The place of research was carried out at SMP Negeri 22 Surabaya. This type of research is descriptive research with a qualitative approach. Data analysis was carried out by drawing conclusions and describing the percentage of students who achieved certain mathematical modeling indicators. The subjects of this study were twenty-six junior high school students in grade VIII. Students were given a test sheet containing AKM problems in the numeracy section that had been adapted to the geometry and measurements content domain. The results showed that in the geometry and measurements content domain, 77% of students are still in the stage of working mathematically. Students are able to make mathematical modelling used to calculate volume using the formula and calculate water volume using debit and time. However, students still have difficulty in interpreting answers and referring the results of answers that have been obtained with mathematical models to the context of everyday life problem situations given in AKM problems in the geometry and measurement content domain. Teachers have an important role in training students to get used to writing answers systematically, so that they are able to provide appropriate solutions when answering the problems given. Hubungan antara matematika dan penerapan konsep matematika mempengaruhi semua aspek kehidupan sehari-hari. Karena adanya hubungan antara matematika dan dunia nyata melalui model matematika, pemodelan matematika dapat membantu siswa dalam memahami hubungan ini. Dalam soal Asesmen Kompetensi Minimum (AKM) berbasis konteks, siswa diminta untuk menyelesaikan soal matematika yang berkaitan dengan dunia nyata. Penelitian ini bertujuan untuk mengetahui kemampuan pemodelan matematis siswa kelas VIII SMP dalam menyelesaikan soal AKM. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Analisis data dilakukan dengan penarikan kesimpulan dan mendeskripsikan persentase banyaknya peserta didik yang mencapai indikator pemodelan matematika tertentu. Subjek penelitian ini adalah dua puluh enam siswa SMP kelas VIII. Siswa diberikan lembar tes yang berisi soal AKM pada bagian berhitung yang telah disesuaikan dengan domain konten geometri dan pengukuran. Hasil penelitian menunjukkan bahwa pada domain konten geometri dan pengukuran, 77% siswa masih dalam tahap bekerja secara matematis. Siswa mampu membuat pemodelan matematika yang digunakan untuk menghitung volume dengan menggunakan rumus dan menghitung volume air dengan menggunakan debit dan waktu. Namun, siswa masih mengalami kesulitan dalam menginterpretasikan jawaban dan menghubungkan hasil jawaban yang telah diperoleh dengan model matematika dengan konteks situasi masalah kehidupan sehari-hari yang diberikan dalam soal AKM pada domain konten geometri dan pengukuran. Guru memiliki peran penting dalam melatih peserta didik agar terbiasa menuliskan jawaban secara sistematis, sehingga mereka mampu memberikan solusi yang tepat saat menjawab pertanyaan-pertanyaan yang diberikan